How might the European Union engage constructively with China in the South China Sea? - LIU, Nengye (Institutional Knowledge at Singapore Management University, 2018)
This article addresses the following questions: How does the South China Sea matter to the European Union? What roles could the EU play in the governance of the South China Sea? In particular, how could the EU effectively engage with China in the South China Sea? The article provides an analysis of the legal basis and policy background for the EU's involvement in the South China Sea governance and explores the EU's interests in the South China Sea.